Meta-analysis of the effect of perioperative injection of Lucentis on intraoperative bleeding in patients with proliferative diabetic retinopathy - GuanGuoqi; ZangJing (眼科学报, 2015)
Background: The effect of perioperative injection of Lucentis on intraoperative bleeding in patients with proliferative diabetic retinopathy (PDR) was systematically evaluated using a meta-analysis. Methods: Reports of surgical eye treatment with and without perioperative intravitreal injection of Lucentis in Medline, the Cochrane Library, PubMed, the Chinese Biomedical Literature Database, and China Academic Journals Full-text Database were included in the study. A meta-analysis was performed on all included literature. A computerized search was performed in the above databases. In addition, relevant books, journals, and conference proceedings and their bibliographies were manually searched. Published literature was screened according to the inclusion and exclusion criteria. Data extraction was performed on included studies. RevMan5.2 software was used for the statistical analyses. Dichotomous variables are presented as odds ratios (ORs) and 95% confidence intervals (CIs). The major indicator was the occurrence of intraoperative retinal hemorrhaging during vitrectomy. Results: A total of seven studies were included in the analysis. The treatment group included 159 eyes and control group included 149 eyes. The amount of intraoperative bleeding in the treatment group (perioperative Lucentis injection) was significantly lower than that in the control group (OR, 56.93; 95% CI: 21.81-148.57, P<0.01). Conclusions: Intravitreal Lucentis injection before a vitrectomy significantly reduced intraoperative bleeding in PDR patients.